Poor Subjective Sleep Quality Among Patients with Cancer and Comorbid Depression: An Opportunity to Inform Screening and Intervention. Issue 1 (2nd January 2023) - Price, Sarah N.; Hamann, Heidi A.; Halaby, Laila; Trejo, Juanita I.; Corella, Fernanda; Weihs, Karen L.
ABSTRACT: Objective: Sleep disturbances are under-identified and under-treated in oncology settings, especially for underserved populations and those with psychiatric comorbidities. This study examined the prevalence and correlates of poor subjective sleep quality as well as clinical sleep recommendations among a socioeconomically and ethnically diverse population of patients with cancer referred for depression management. Methods: Participants were 140 adults with cancer who screened positive for depression through routine, practice-based assessment with the Patient Health Questionnaire (PHQ-9 ≥ 8) and were referred to a study of collaborative care for depression. Demographics, clinical characteristics, subjective sleep quality, and sleep recommendations received were self-reported by patients prior to intervention. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), general health status was measured using the Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10, and depressive symptoms were measured using the PHQ-9. Results: Of 138 patients with complete data, 123 (89.1%) reported poor sleep quality, and 87 (63%) met the threshold for possible insomnia. The strongest correlates of poor subjective sleep were female gender ( β  = 0.19, p =  .02), greater depressive symptom severity ( β  = 0.28, p =  .001), and worse physical health ( β  = −0.19, p =  .04). Of 118 patients reporting problems with sleep since their cancer diagnosis, 95 discussed the issue with a medical provider; medications were recommended most often (37; 38.9%); only 9 (9.5%) received recommendations for cognitive-behavioral therapy for insomnia (CBT-I) or other CBT. Conclusions: Patients with cancer seeking treatment for depression report very high rates of poor subjective sleep quality and insomnia, underscoring the importance of providing and referring to guideline-concordant sleep interventions in oncology supportive care contexts.